Biomass chitosan derived 3D hierarchical porous carbon framework: Green synthesis and efficient polysulfide confinement. (December 2022) - Zeng, Q.; Ma, X.; Liang, F.; Jiang, M.; Zhu, Y.; Zhu, J.; Shen, P.K.
Abstract: In this study, we synthesize a nitrogen-doped hierarchical porous carbon framework with an ultrahigh surface area (a Brunauer-Emmett-Teller surface area of 2514.79 m 2 /g) rich in micropores/mesopores using a template-free strategy utilizing low-cost biomass chitosan as a precursor. This environmental-friendly non-organic potassium/lithium hydroxide system not only dissolves chitosan but also activates carbon framework. Moreover, rational pore structure and physical properties (e.g. conductivity) are realized by adjusting the heat-treatment temperature. The nitrogen-doped hierarchical porous carbon framework/S cathodes reach high area capacities of 4.02 mAh/cm 2 and 6.02 mAh/cm 2 at 0.2C with high sulfur loadings of 4 and 8 mg/cm 2, which can be attributed to the immobilization of lithium polysulfide via micropores/mesopores combined with heteroatom doping. In-situ Raman and X-ray diffraction tests further confirm that the rich micropores/mesopores of the carbon host can act as an active site for the inhibition and catalytic conversion of polysulfide. It is a new strategy and direction for recycling biomass chitosan and also provides a reference for the practical and commercial large-scale application of lithium sulfur batteries. Graphical abstract: Image 1 Highlights: Non-organic potassium/lithium hydroxide system not only dissolves chitosan but also activates carbon framework. nitrogen-doped hierarchical porous carbon framework (NHPCF)/S reaches an ultralow decay rate of 0.014% at 2C for 1000 cycles NHPCF/S reaches a high area capacity of 6.02 mAh/cm 2 at 0.2C with sulfur loadings of 8 mg/cm 2 In-situ Raman and X-ray diffraction are used to investigate the electrochemical mechanism in NHPCF/S